Adoption of information and communication technology for development: A case study of small and medium enterprises in Bangladesh. (September 2016) - Hoque, Md. Rakibul; Saif, Abu Naser Mohammad; AlBar, Adnan Mustafa; Bao, Yukun
Information and Communication Technologies (ICTs) play a key role in today's business environment. ICTs also give small firms a competitive advantage in the new economy. However, little empirical research has addressed the issues of use, impact and adoption of ICTs in Small and Medium Enterprises (SMEs), especially in rural areas of developing countries. The objective of this study is to identify the impact of ICTs and the factors that influence the adoption of ICTs in SMEs located in rural areas of Bangladesh. This article follows a qualitative and quantitative research approach based on a case study and structured questionnaires. The regression analysis showed that awareness of benefits, government support, top management support, and financial support are important determinants of the adoption of ICTs in rural SMEs in Bangladesh. This article also highlights the limitations that SMEs have in using ICTs and makes recommendations on how to overcome them.